Sistem Informasi Manajemen RT/RW Berbasis Website - Hidra Amnur; Witri Wulandari; Cipto Prabowo (SOTVI - Society of Visual Informatics, 2024)
The web-based Rukun Tetangga (RT) / Rukun Warga (RW) Management Information System using the CodeIgniter 4 Framework is an application development project that aims to increase efficiency and effectiveness in managing population data and public services at the RW level. This application is designed to make it easier to submit letters online, as well as monitor the letter completion process. This application development adopts the Waterfall method to ensure structured and planned development. MySQL database is used as a data storage system. This website-based application was built using the PHP programming language and is supported by the CodeIgniter 4 Framework. With the implementation of this application, it is hoped that local communities can submit letters more easily, and monitoring the letter completion process will become more transparent. It is also hoped that this application can help improve the quality of public services at the RW level, provide easy access, and speed up the service process for residents.